Shadowy Presences: Mobility, Labor and Absence in the Work of Dominican Photographer Fausto Ortiz - Garrido Castellano, Carlos (2017)
This article aims to examine the ways in which contemporary art from the Caribbean, and specifically from the Dominican Republic, is analyzing mobility and human trafficking within a transnational context. In this case I will critique the work of the photographer Fausto Ortiz (Santiago de los Caballeros, 1970), who has reflected recently on the consequences of migration and displacement for Dominican cultural politics. Rather than addressing the representation of marginalized sectors and marginal forms of economy in the particular case of the Dominican Republic, I argue that Ortiz’s photographic practice deepens and broadens the debates about race, citizenship and social inequality, forcing his audience to consider those issues as a central part of the everyday. While addressing those issues, this article tries to insert Ortiz’s photographic practice within international debates on mobility, border practices and displacement.